The Impact of Eddies on Nutrient Supply, Diatom Biomass and Carbon Export in the Northern South China Sea - Shih, Yung‐Yen; Hung, Chin‐Chang; Tuo, Sing‐how; Shao, Huan‐Jie; Chow, Chun Hoe; Muller, François L. L.; Cai, Yuan‐Hong (Frontiers in Earth Science, 2020)
We have investigated the effect of eddies (cold and warm eddies, CEs and WEs) on the nutrient supply to the euphotic zone and the organic carbon export from the euphotic zone to deeper parts of the water column in the northern South China Sea. Besides basic hydrographic and biogeochemical parameters, the flux of particulate organic carbon (POC), a critical index of the strength of the oceanic biological pump, was also measured at several locations within two CEs and one WE using floating sediment traps deployed below the euphotic zone. The POC flux associated with the CEs (85 ± 55 mg-C m−2 d−1) was significantly higher than that associated with the WE (20 ± 7 mg-C m−2 d−1). This was related to differences in the density structure of the water column between the two types of eddies. Within the core of the WE, downwelling created intense stratification which hindered the upward mixing of nutrients and favoured the growth of small phytoplankton species. Near the periphery of the WE, nutrient replenishment from below did take place, but only to a limited extent. By far the strongest upwelling was associated with the CEs, bringing nutrients into the lower portion (~ 50 m) of the euphotic zone and fueling the growth of larger-cell phytoplankton such as centric diatoms (e.g. Chaetoceros, Coscinodiscus) and dinoflagellates (e.g. Ceratium). A significant finding that emerged from all the results was the positive relationship between the phytoplankton carbon content in the subsurface layer (where the chlorophyll a maximum occurs) and the POC flux to the deep sea.